Factors That Affect the Trust and Interest of Tourists to the Tourist Attractions of Gunung Payung Beach, Kutuh - Dewi, Ida Ayu Kusuma; Utama, I Putu; Witarsana, I Gusti Agung Gede (Universitas KH. Abdul Chalim Mojokerto, 2026)
Gunung Payung Beach, located in Kutuh, is one of the tourist attractions that still faces challenges in the form of low visitor numbers. This issue is influenced by several factors, including destination image, user-generated content (UGC), and the level of trust that develops among tourists. Destination image and user-generated content are crucial factors in shaping tourists’ perceptions, while trust in the destination serves as a psychological mechanism that mediates the influence of these factors on visit intention. This study aims to analyze the factors influencing trust and tourists’ visit intention at Gunung Payung Beach, with a focus on the mediating role of trust in this relationship. The research adopts a quantitative approach using Structural Equation Modeling-Partial Least Square (SEM-PLS) for data analysis. Data were collected through the distribution of questionnaires to 250 respondents who expressed interest in visiting Gunung Payung Beach, using a purposive sampling technique. The findings reveal that destination image and UGC have a positive and significant effect on both trust and visit intention. Furthermore, trust is proven to have a significant influence on visit intention and serves as a mediating variable that explains the process by which destination image and UGC can drive tourists’ intention to visit. These findings emphasize that trust is a key factor in shaping sustainable visit intention. Theoretically, this research contributes to the development of studies on tourist behavior, while practically, it provides recommendations for the management of Gunung Payung Beach to strengthen the destination image, improve service and facility quality, and strategically manage UGC to build trust and enhance the competitiveness of the destination.